Antitumor activity of methyl (Z)-2-(isothioureidomethyl)-2-pentenoate hydrobromide against leukemia cell lines via mitotic arrest and apoptotic pathways - Assunção, Laura Sartori; Kretzer, Iara Fabrícia; Sierra Restrepo, Jelver Alexander; de Mello Junior, Leônidas João; Silva, Adny Henrique; de Medeiros Oliveira, Eliana; Ferreira, Misael; Sá, Marcus Mandolesi; Creczynski-Pasa, Tânia Beatriz (Biochimica et biophysica acta. General subjects, 2019)
In a previous study, we described a series of 28 aryl- and alkyl-substituted isothiouronium salts with antitumor activity and selectivity toward a leukemia cell line. Among the synthesized compounds, methyl (Z)-2-(isothioureidomethyl)-2-pentenoate hydrobromide (IS-MF08) showed conspicuous activity. In the present study, we investigated the mechanism of action of IS-MF08. Our results showed that its mechanism most likely is related with the membrane receptor Fas and subsequent activation of the extrinsic cell death pathway, triggered by a decrease in the levels of the anti-apoptotic protein Bcl-2 and caspase-8 and -3 cascade activation, causing DNA damage and mitotic arrest. IS-MF08 also caused an increase in intracellular ROS, endoplasmic reticulum (ER) stress, and mitochondrial membrane permeabilization, resulting in organelle degradation as an attempt to reestablish cell homeostasis. Furthermore, cells exposed to IS-MF08 combined to an autophagy inhibitor were less susceptible to compound's cytotoxicity, suggesting that autophagy makes part of its mechanism of action. These data support the hypothesis that IS-MF08 acts by the apoptosis extrinsic pathway and possibly by autophagy as mechanisms of cell death. •Isothiouronium salts showed selective antitumor activity against leukemia cells.•The isothiouronium salt MF08 induces mitotic block in leukemia cells.•Its mechanism of action involves extrinsic apoptosis pathway.